KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE - Marzuki Ahmad; Ilham Sahdi Lubis; Dwi Putria Nasution; Rohani Rohani (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to describe the improvement of students' Mathematical Critical Thinking Ability (MCTA) through the Think Pair Share (TPS) Cooperative learning model. This type of research is a quasi-experimental with Nonequivalent Control Group Design. The population in this study were students of class X SMA Negeri 2 Padangsidimpuan. Through purposive sampling, research samples were taken from class X IIS 2 as the experimental group and class X IIS 1 as the control group. The research instrument includes an observation sheet on learning activities and student MCTA tests which include pretest and posttest questions. Data analysis using N-gain score, t-test. Analysis of the observational data showed the average value of learning management with a score of 4.48. Obtaining N-Gain with t-test on student MCTA data obtained a significance of <0.05. The average acquisition of the N-gain MCTA index of students in the experimental class was 0.42 and in the control class was 0.29. Through two-way ANOVA at the gender level with a learning model to improve students' MCTA, a significance of 0.736>0.05 was obtained. It was concluded that the application of TPS-type cooperative learning in improving students' MCTA was good. The TPS-type cooperative learning model's improvement was better than the regular MCTA of students.